Effect of selective serotonin reuptake inhibitor treatment on the prognosis of patients with medication overuse headache. Issue 12 (March 2018) - Fang, Jinghuan; Zhang, Yang; Chen, Ning; Guo, Jian; Zhou, Muke; He, Li
Abstract : Abstract: Medication overuse headache is a disabling headache disorder. Withdraw treatment plus preventive medication may lead to a better outcome. However, the effect of selective serotonin reuptake inhibitor on the treatment of medication overuse headache is still unknown. In this study, we followed up medication overuse headache patients diagnosed at the West China Hospital at an average follow-up duration of 1.5 years to analyze patients' outcomes and relapse. We used logistic regression to assess the relationship between patient medication and effect of withdrawal treatment. We used COX (cox regression model) regression analysis to assess the relationship between withdrawal treatments and relapse rate in patients. A total of 72 medication overuse headache patients were enrolled in this study, of which 14 (19.4%) failed to withdraw therapy, 58 got a good response to withdraw therapy. Among responders, there are 5 (8.6%) relapse patients. Selective serotonin reuptake inhibitor treatment can increase the effect of withdrawal therapy (odds ratio [OR] = 0.016, 95% confidence interval [CI]: 0.003, 0.091, P  < .001) and it was an important predictor of patients' outcome (hazard ratio [HR] = 0.255, 95%CI: 0.09–0.724). Selective serotonin reuptake inhibitor can increase the therapeutic effect in medication overuse headache withdrawal therapy and can reduce the risk of relapse.